A New (3, 6)-Connected Heterometallic Coordination Polymer: Therapeutic and Protective Effect on Ischemic Cerebral Infarction - Jia Ma; Jianer Wang; Yuping He; Yiwei Huang; Yejun Chen (Journal of Chemistry)
Solvothermal reaction of 4,4’,4’-nitrilotribenzoic acid (H3TCA) with Ca(NO3)2·4H2O and Cd(NO3)2·4H2O successfully afforded a heterometallic compound, that is, [Cd2Ca(TCA)2(DMA)2(H2O)3]n·2n(DMA) (1, DMA = N,N’-dimethylacetamide). The structure of 1 was further characterized through EA, diffraction of single crystal X-ray, and thermogravimetric analysis (TGA) together with powder X-ray diffraction (PXRD). Moreover, complex 1’s luminescent performance in solid state was also discussed at environmental temperature. The applications on the ischemic cerebral infarction therapy were evaluated, and the specific mechanism was investigated at the same time. Firstly, the hypersensitivity C-reactive protein (hs-CRP) content in human brain microvascular endothelial cell (HBMEC) was measured with real-time reverse transcription-polymerase chain reaction (RT-PCR). Then, interleukin-18 and interleukin-1β content released through the HBMEC was detected with enzyme-linked immunosorbent assay (ELISA).